APLIKASI KONSEP BALANCE SCORECARD SEBAGAI TOLOK UKUR KINERJA PEMERINTAH DAERAH - Machmud, Senen (Majalah Bisnis & IPTEK, 2021)
The concept of the balanced scorecard (BSC) which is substantially intended to improve customer service performance (community), adopted particularly relevant in the development of local financial management in the future. Conceptually BSC is in line with the policy direction of the current financial management, namely in order to achieve good governance performance, Expenditure and Budget (APBD) must be arranged with the budget performance. Budgeting and Expenditure (APBD) must be done to achieve the outputs, outcomes, benefits, and impact, in accordance with the vision and mission that has been set. Keywords: balance scorecard; budget performance.